Student and Lecture Attendance on Moodle Elearning Based on Cloud Infrastructure - Laksana, Eka Angga (CENTRAL ASIA AND THE CAUCASUS, 2022)
E-learning is a unit where there is collaboration with academics and IT unit. Here we develop several technologies that can assist academic administration, especially those closely related to the learning process and evaluation. Of course, this cannot happen without the support and tools from the IT Bureau, such as servers and web hosting, which are a place for the system we have developed. Moodle is the main application that is the main operation of e-learning at Widyatama University, but Moodle itself is not enough to solve higher education learning problems, especially at Widyatama University. The following are some of the main problems that are not a feature of Moodle itself so it needs developments that have been carried out by the elearning unit.